Legal instruments for countering means and conditions that affect the sport result - Pukhov Artyom А.; Tkharyova, Marina G. (Journal of the Belarusian State University. Law, 2021)
The article examines the legal status of specific categories of athletes with advantages. It also makes the case for the need to regulate the legal relations of uses of technical and medical means that affect competitive results. The article presents the concept of technological doping. It is proposed to introduce a separate category in competitions, taking into account the functionality of athletes with individual physiological differences.